Microlearning in Undergraduate Medical Education: A Systematic Review and Meta-Analysis of Impact on Knowledge, Skills, and Retention - Saranya Rajamanickam; Vijaykumar Rajendran; Manoharan PS (National Journal of Community Medicine, 2026)
Background: Microlearning delivers content in short, focused units and is increasingly used in medical education, but consolidated quantitative evidence for undergraduate training remains limited. This systematic review and meta-analysis evaluated the impact of microlearning on knowledge, skills, and retention among undergraduate medical students. Methods: A comprehensive literature search spanning PubMed, Scopus, Web of Science, and Google Scholar were conducted from database inception through January 2025. The inclusion criteria covered experimental research comparing microlearning methods against conventional instructional techniques among undergraduate medical students. Although the review protocol lacked prospective registration, study quality was appraised using RoB 2 and ROBINS-I tools. Hedges' g standardized mean differences (SMD) were aggregated via a restricted maximum likelihood (REML) random-effects model. Results: A total of seven studies encompassing 1,674 learners comprising two randomized controlled trials and five quasi-experimental or non-randomized investigations met the selection criteria. Microlearning delivered a statistically significant enhancement in learner outcomes compared to traditional education (SMD = 0.90; 95% CI: 0.57-1.22; p